The Influence Of Managerial Ability And Foreign Ownership On Firm Value: Income Smoothing As Mediating Variable - Suwandi Ng; Livia Chandra (Pusat Publikasi Nusantara, 2023)
This research is aimed to investigate the effect of managerial ability and foreign ownership to decrease income smoothing as a mediating effect influence on value of firm. This research uses logistic regression analysis method to investigate the effect of managerial ability and foreign ownership on income smoothing, and multiple regresion linear to investigate the effect of managerial ability, foreign ownership, and income smoothing on value of firm, and Sobel's test to investigate the effect of income smoothing as mediating variable. The results of this research shown that managerial ability have not a significant effect on income smoothing and firm performance, but foreign ownership have a significant effect on income smoothing and value of firm, and income smoothing have a significant effect on value of firm. In addition, Sobel's test results showed that income smoothing do not mediate the effect of managerial ability and foreign ownership on value of firm